Psychostimulants and movement disorders. - Andres eAsser; Pille eTaba (Frontiers in Neurology, 2015)
Psychostimulants are a diverse group of substances with their main psychomotor effects resembling those of amphetamine, methamphetamine, cocaine or cathinone. Due to their potential as drugs of abuse, recreational use of most of these substances is illegal since the 1971 Convention on Psychotropic Substances. In recent years, new psychoactive substances have emerged mainly as synthetic cathinones with new molecules frequently complementing the list.Psychostimulant related movement disorders are a known entity often seen in emergency rooms around the world. These admissions are becoming more frequent as are fatalities associated with drug abuse. Still the legal constraints of the novel synthetic molecules are bypassed. At the same time chronic and permanent movement disorders are much less frequently encountered. These disorders frequently manifest as a combination of movement disorders. The more common symptoms include agitation, tremor, hyperkinetic and stereotypical movements, cognitive impairment, and also hyperthermia and cardiovascular dysfunction.The pathophysiological mechanisms behind the clinical manifestations have been researched for decades. The common denominator is the monoaminergic signaling. Dopamine has received the most attention but further research has demonstrated involvement of other pathways. Common mechanisms linking psychostimulant use and several movement disorders exist.